ANALISIS RENDAHNYA TINGKAT KEPATUHAN WAJIB PAJAK PBJT PERHOTELAN (STUDI KASUS PADA BAPENDA KOTA MADIUN) - Widya Kusumaningsih; Mia Rosmiati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study examines the issue of low taxpayer compliance in the hospitality sector under the Specific Goods and Services Tax (PBJT) in Madiun City. Taxes play an important role in supporting regional development, particularly in strengthening local revenue; however, taxpayer compliance remains a key challenge at the local level. In Madiun City, although hotel tax revenue consistently exceeded the target during the 2020–2024 period, the level of taxpayer compliance remains relatively low. This condition indicates a discrepancy between revenue performance and compliance behavior among taxpayers. This research applies a qualitative approach using a case study conducted at the Regional Revenue Agency (Bapenda) of Madiun City. Data were collected through interviews, documentation, and literature review, and analyzed using qualitative techniques involving data reduction, data display, and conclusion drawing. The findings show that taxpayer compliance is influenced by internal, external, and relational factors. Internal factors such as negligence, lack of discipline, and weak administrative management are identified as the main causes of low compliance. Meanwhile, external and relational factors tend to function as supporting conditions rather than primary determinants. Therefore, improving taxpayer compliance requires more focused efforts, particularly in encouraging behavioral changes and strengthening administrative practices to support sustainable regional fiscal capacity.